2004
DOI: 10.1016/j.jcrs.2004.04.069
|View full text |Cite
|
Sign up to set email alerts
|

Effect of instrument rotation on handheld keratometry

Abstract: Handheld keratometry was in agreement with topographic keratometry. However, practitioners should adjust the axis manually according to the direction and amount of rotation. The difference between handheld and topographic keratometry increased with the rotational effect, which was seen with vector representation. Practitioners are advised to use the handheld keratometer in the upright position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
(5 reference statements)
0
7
0
Order By: Relevance
“…However, few studies have assessed the comparability of corneal astigmatism and axis location, both of which play an important role in the surgical correction of cylindrical errors. [27][28][29] Moreover, to our knowledge, ours is the first study to compare these astigmatic parameters between autokeratometry and corneal topography, both of which are quick and convenient methods for measuring these variables in a clinical setting. Table 4 shows a summary of previous studies of agreements in corneal astigmatism, axis location, and astigmatic vector components measurements between keratometry and corneal topography.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, few studies have assessed the comparability of corneal astigmatism and axis location, both of which play an important role in the surgical correction of cylindrical errors. [27][28][29] Moreover, to our knowledge, ours is the first study to compare these astigmatic parameters between autokeratometry and corneal topography, both of which are quick and convenient methods for measuring these variables in a clinical setting. Table 4 shows a summary of previous studies of agreements in corneal astigmatism, axis location, and astigmatic vector components measurements between keratometry and corneal topography.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the 2 devices showed poor agreement between measurements of corneal astigmatism and axis location, possibly as a result of an irregular corneal surface. Lam et al 29 compared J0, J45, and axis location between a handheld autokeratometer and a corneal topographer. The handheld keratometer was in agreement with the topographic keratometer; however, the differences between the 2 devices increased with the rotational effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the power vector method was applied, the changes were still small and within onesixth of a dioptre. The vector representation is more sensitive in revealing corneal power changes 31,32 however, the order of change is too small to be considered as clinically significant.…”
Section: Discussionmentioning
confidence: 99%
“…With hand-held keratometry, incorrect orientation of the instrument and the patient causes inaccuracy in the measurement. 66 Therefore, it is essential with any measurement of corneal power that a vertical head and instrument orientation is achieved and maintained. The most common method in the literature for establishing the correct keratometric power and axis is automated keratometry with the IOLMaster (Carl Zeiss, California, Germany) and confirmation of this result with a computerised topographer, although which is chosen when they are disparate is not obvious.…”
Section: Aligning the Toric Iolmentioning
confidence: 99%